Implementation Of Work Discipline, Motivation, And Compensation On Employee Performance Of PT. Wan Tobacco Cigaret Sidoarjo - Moch Nur Dieny Faylasuf; Hasan Ubaidillah; Rifdah Abadiyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of work discipline, motivation, and compensation on employee performance at PT. Wan Rokok Tembakau Sidoarjo. This study uses descriptive and verification methods to explore the relationship between work discipline, motivation, and compensation. Data were collected using questionnaires, observations, and literature reviews involving a sample of 100 employees selected using simple random sampling. Hypothesis testing was carried out using multiple linear regression analysis with the help of the SPSS version 25 program. The results of the study indicate that work discipline, motivation, and independence have a significant effect on employee performance, both partially and simultaneously. This study confirms that work discipline, motivation, and recovery are strategic elements in effective human resource management, especially in improving employee performance. By paying attention to and developing all three in a balanced manner, the company can create a work system that is oriented towards results, sustainable, and competitive.